2021
DOI: 10.1021/acs.jafc.1c00878
|View full text |Cite
|
Sign up to set email alerts
|

Can Serum be a Match for Urine in the Regulatory Analysis of Boldenone in Cattle? A Systematic Comparison Between Detection Window, Stability, and Enzymatic Hydrolysis

Abstract: This work involved a systematic comparison between serum and urine for the monitoring of anabolic androgenic steroids in livestock. Incurred samples were collected over 120 days from crossbred steers treated with intramuscular injections containing boldenone undecylenate. Independent high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/ MS) methods were used for the assessment of the respective detection windows, which were larger for serum samples. Both matrices presented adequate performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…Thus, in both stability studies, the STN residues were stable under all of the evaluated conditions, which reinforces that the serum matrix is sufficiently stable to be used as a matrix of choice for detecting STN treatment in steers when it comes to stability. 38,42,43 The obtained concentration values for MS A , MS E , and F calc from both stability studies are presented in Table 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, in both stability studies, the STN residues were stable under all of the evaluated conditions, which reinforces that the serum matrix is sufficiently stable to be used as a matrix of choice for detecting STN treatment in steers when it comes to stability. 38,42,43 The obtained concentration values for MS A , MS E , and F calc from both stability studies are presented in Table 3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The hydrolysis of β-agonist-conjugated ester residues in the muscles is necessary before extraction. 41 Their conjugates mostly exist in the form of glucuronide or sulfate. Ractopamine, tulobuterol, and salbutamol are selected to prepare the incurred samples because they can frequently form conjugate states in the organism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The hydrolysis of β-agonist-conjugated ester residues in the muscles is necessary before extraction . Their conjugates mostly exist in the form of glucuronide or sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…14 Stability studies concerning anabolic steroids were reported by Rocha et al, in which bovine urine and serum presented stability during 196 days at −20 °C. 19 De Wilde et al evaluated human urine for the stability study of steroid conjugates, in which a stable result was obtained after six freeze−thaw cycles and after 10 years of storage at −20 °C. 20 De Clercq et al studied bovine feces stability for six glucocorticoids; the work explored redox conditions, influence of ethanol addition, and lyophilization and also included freeze−thaw and long-term studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Stability studies concerning anabolic steroids were reported by Rocha et al, in which bovine urine and serum presented stability during 196 days at −20 °C . De Wilde et al evaluated human urine for the stability study of steroid conjugates, in which a stable result was obtained after six freeze–thaw cycles and after 10 years of storage at −20 °C .…”
Section: Introductionmentioning
confidence: 99%